Exploring the Ex-Hoogere Kweekschool Purworejo as a Historical Learning Resource for High School Students in Purworejo Regency - Ranita Nazara; Aman Aman; Amirul Syafiq (STAI Hubbulwathan Duri, 2024)
This study investigates the educational potential of the Ex Hoogere Kweekschool (HKS) Purworejo heritage site as an interactive and contextual resource for high school history education in Purworejo Regency. Employing a qualitative approach with descriptive analysis, the research integrates observation, interviews, and document review methods. Observations evaluate the site's use in educational settings, while interviews with teachers, students, and site managers offer insights into its application in history lessons. Document reviews provide a historical context and outline prior educational uses of the site. Findings reveal that the Ex HKS Purworejo, built in 1915 by architect BOW J.Th. van Hoytema, significantly enhances students' learning experiences. The site's architecture and historical significance facilitate contextual history education, enabling students to engage directly with the historical environment. Despite its potential to accommodate up to 75 students and teachers and its preservation of 17 buildings in the Indies architectural style along with other authentic elements like ancient garden lamps, the site's use in history education at SMA Negeri 7 Purworejo and throughout the district remains suboptimal. The study emphasizes the importance of incorporating authentic historical resources like Ex HKS Purworejo into the history curriculum. This approach is vital for educators and policymakers in Purworejo Regency to develop strategies that optimize the use of cultural heritage sites in education. Enhancing the use of Ex HKS Purworejo and similar sites can enrich learning materials and offer students dynamic, meaningful learning experiences, fostering a deeper appreciation for their local cultural heritage.